ASSESSMENT OF EFFICACY AND SAFETY OF COMBINED MICROINVASIVE LASER-SURGICAL TREATMENT OF RHEGMATOGENOUS RETINAL DETACHMENT - A.V. DOGA; D.O. SHKVORCHENKO; L.A. KRYL; M.R. TAEVERE (Avicenna Tajik State Medical University, 2020)
Objective: To evaluate the efficacy and safety of combined laser-surgical treatment of rhegmatogenous retinal detachment (RRD). Methods: The 32 eyes from 32 patients with a local RRD due to horseshoe tear were enrolled. In addition to standard examination, all patients underwent multispectral laser scanning and wide-field optical coherence tomography (WFOCT) to determine the extention and localization of vitreoretinal tractions (VRT). All patients underwent the combined microinvasive laser-surgical technology of RRD treatment, including YAG-laser excision of the VRT area, pneumatic retinopexy, and barrier laser photocoagulation around the retinal tear after complete retinal attachment (2-3 days). The post-operative examination was performed on days 3 and 7, and in 3, 6, 12, 18, and 24 months. The follow-up period was 2 years. Results: Retinal attachment was achieved in 30 patients (93.8%). The retina did not attach in 2 cases (6.4%) - in a patient with pseudophakia and in a patient who did not follow the recommendations on the proper head position after surgery. The recurrence of retinal detachment occurred in 2 cases (6.7%) as a result of the new tears formation in lower parts of the fundus periphery. The rest of the patients had a stable anatomical and functional result and no recurrence of the disease during the follow-up period. In 2 cases (6.7%) post-operative WFOCT revealed an additional zone of VRT in the adjacent areas to primary retinal tear which could not be visualized when retina was detached. These patients underwent additional barrier laser photocoagulation around revealed areas. No relapses occurred in these patients. Clinically insignificant retinal bleeding was observed in 4 cases (12.5%) during combined laser angiotomy. Full haemostasis was achieved by the 3-mirror contact lens pressure on the eye. Conclusion: The presented technology demonstrates efficiency in 93.8% of cases after a single surgical intervention. The advantage of the technology is the complete elimination of VRT, as the main factor of the disease pathogenesis, which increases the anatomical efficacy of surgery and reduces the risk of recurrence. The micro-invasiveness and low trauma of this type of treatment help to minimize complications and accelerate the rehabilitation of patients. Further study of this technology with a large number of patients and a long follow-up period is required.